Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/np800656r
|View full text |Cite
|
Sign up to set email alerts
|

Tetranortriterpenoids from the Leaves of Cipadessa cinerascens

Abstract: Seven known and six new tetranortriterpenoids, cineracipadesins A-F (1-6), were isolated from the leaves of Cipadessa cinerascens. Compound 1 has a mexicanolide-type structural skeleton with a rare 9alpha,11alpha-epoxide ring; compound 2 has a methyl angolensate-type structure with 9,11-dihydroxy groups, representing the first example of a precursor of a trijugin-type limonoid; and 3 is the first reported methyl angolensate-type limonoid with a ketone group at ring C. Their structures were determined with exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
(41 reference statements)
0
31
0
Order By: Relevance
“…The strong IR absorptions at 3443 and 1729 cm −1 implied the presence of hydroxyl and ester carbonyl groups, respectively. The 1 H-NMR (Table 1) [7,8]. Extensive analysis of 2D NMR ( 1 H-1 H COSY and HMBC) spectra, a tigloyl moiety, an isobutyryl group, and one acetoxyl group were inferred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong IR absorptions at 3443 and 1729 cm −1 implied the presence of hydroxyl and ester carbonyl groups, respectively. The 1 H-NMR (Table 1) [7,8]. Extensive analysis of 2D NMR ( 1 H-1 H COSY and HMBC) spectra, a tigloyl moiety, an isobutyryl group, and one acetoxyl group were inferred.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the planar structure of trichinenlide U (1) was elucidated as indicated. [7,8]. Extensive analysis of 2D NMR ( 1 H-1 H COSY and HMBC) spectra, a tigloyl moiety, an isobutyryl group, and one acetoxyl group were inferred.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular formula, C 34 H 42 O 13 , and a characteristic low-field H-17 proton at δ 5.38 (1H, s) in the 1 H NMR spectrum, as well as the characteristic carbonyl group at C-1 (δ C 213.0) in the 13 C NMR spectrum, strongly suggested that 1 was a mexicanolide-type limonoid. 13,14 The 1 H and 13 C NMR data (Tables 1 and 2) of 1 including the fully substituted olefinic resonances at δ C 135.8 and 140.4 due to C-8 and C-14, respectively, were similar to those of augustineolide. 15 The major differences between them were the absence of isobutyryl group in compound 1, and the locations of the substituent.…”
Section: Resultsmentioning
confidence: 98%
“…The information above strongly suggested that 5 was a mexicanolide-type limonoid. 13,14 The key HMBC cross-peaks of Hβ-30/C-8, C-9, H-18/C-13, C-14 and H-17/C-16 revealed a conjugated vinyl-vinyl-lactone unit from C-9 to C-16. The planar structure of 5 was further confirmed by detailed 2D NMR analysis (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation